Modelling of Radio-Frequency Heating of Piles of Pinus Radiata Wood - Vasco-Calle, D (North Carolina State University, 2018)
The present work studied the numerical modelling of heat transfer in a pile of Pinus radiata samples of a square cross-section by using radio frequency heating. More precisely, the study focused on the effects of the energy transferred to a dielectric material (wood) from an electromagnetic field, which required the calculation of the dielectric loss factor and its correlation with conservative equations. In this way, the temperature distribution across Pinus radiata samples was obtained through the integration of the energy equation using the finite volume method. The numerical results were compared to experimental data obtained from three experiments of radio-frequency heating of wood samples of a cross-sectional area of 4 in × 4 in, 3.1-m-long, and 20 cm of separation between plates. According to the observed linear behavior of the heat transfer process, the numerical results of the transient variation of temperature were in agreement with the experimental data.